Board Structure and Firm Performance: Evidence from French Firms Listed in SBF 120 - AMMARI, Aymen Ben Bechir; KADRIA, Mohamed; ELLOUZE, Abderrazak (International Journal of Economics and Financial Issues, 2014)
Using a sample of 40 French companies listed on the SBF 120 for the period 2002-2009, we examine if board structure (board size, independence of its members and the cumulative functions of decision and control) relate to their performance. To test the validity of our hypothesis, which states the existence of a certain deterministic between the board structure and financial performance measured by four different ratios, namely ROA, ROE, Tobin's Q and Market to Book, we have developed four dynamic panel system GMM approach to control for relevant sources of endogeneity (simultaneity, reverse causality and unobserved heterogeneity). Our results support the idea, commonly accepted, that board structure is a determinant factor for French firm performance. Keywords: Board of Directors; board size; independence of the board; accumulation of functions; financial performance; system GMM. JEL Classifications: G30; G34; J44; L25